Узагальнена теорема про мінімакс та критичні точки багатозначних відображень - Melnik, V. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The classical asymmetric minimax theorem for the class of continuous mappings of sets of two players’ strategies is generalized on the class of multiciphered semicontinuous on the top mappings with compact images. The generalized minimax theorem is applied to prove theorems about existence and properties of multiciphered mappings critical points in topologic spaces.